An Analysis on Reading Strategies based on Metacognitive Awareness and Gender - Chandra Fauzi; Ashadi Ashadi (Lingua Pedagogia, 2019)
This article is based on survey research which sought to identify the reading strategies used by the first-semester graduate students and to reveal the most dominant strategies used by students of different gender. The participants of this study were first-semester graduate students (N = 43) of a state teacher college. A five-point Likert Scale questionnaire named SORS (Survey of Reading Strategies) was deployed to collect the data concerning the use of reading strategies. The findings demonstrated that the first-semester students were greatly conversant in reading strategies with overall mean score of 3.82 which means a high level of awareness. The first-semester students consecutively preferred Problem Solving Strategies to Global Reading Strategies or Support Reading Strategies eventhough all of these three subscales fell into highly-used strategy. Female students were found to use the strategies more frequently that their male counterparts did. Also, the results of individual reading strategies use revealed that both genders tended to reread the text and to circle or underline information in the text to help them understand what they read. However, pedagogical implications on the use of metacognitive strategies that would help students activate their higher order thinking skills in reading needs to be given attention. Keywords: reading strategies, metacognitive awareness, gender